Female habitat choice as a determinant of the reproductive success of the territorial male marine iguana (Amblyrhynchus cristatus). - Rauch, N. (1985)
BIB Now: 5774
English
365
Keywords: BH, MI, EC -- Female habitat choice as a determinant of the reproductive success of the territorial male marine iguana (Amblyrhynchus cristatus).